2020
DOI: 10.1155/2020/8060259
|View full text |Cite
|
Sign up to set email alerts
|

Altered Body Composition and Increased Resting Metabolic Rate Associated with the Postural Instability/Gait Difficulty Parkinson’s Disease Subtype

Abstract: Background. Weight loss in Parkinson’s disease (PD) patients is a common but poorly understood manifestation. Several studies have reported that weight changes could be related to motor symptoms, drug side effects, dysphagia, depression, and/or dementia. Weight loss in PD is not a benign phenomenon and it has several clinical and prognostic implications with increased morbidity and mortality. Thus, it is crucial to determine nutritional changes in PD patients in order to prevent malnutrition and improve their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(67 reference statements)
1
3
0
Order By: Relevance
“…Overall, after adjusting for several confounders, females with PD, with low energy intake and low physical activity, were at higher risk for skeletal muscle wasting. Of note, when we compared weight between PD and family members, we did not find any statistical difference in agreement with previous studies 28–30 . In contrast, longitudinal studies have observed decreases and increases of weight in PD patients over time 4,31–33 .…”
Section: Discussionsupporting
confidence: 89%
“…Overall, after adjusting for several confounders, females with PD, with low energy intake and low physical activity, were at higher risk for skeletal muscle wasting. Of note, when we compared weight between PD and family members, we did not find any statistical difference in agreement with previous studies 28–30 . In contrast, longitudinal studies have observed decreases and increases of weight in PD patients over time 4,31–33 .…”
Section: Discussionsupporting
confidence: 89%
“…The modest reduction in resting energy expenditure in PD from 2–3 weeks of a KD of approximately 100 kcal is a novel finding. This may be interesting to track in a future study to assess whether it is correlated with PD symptoms, as, for instance, a prior study showed an elevated metabolic rate in the postural instability/gait disorder subtype [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 5-year follow-up study found that weight loss heightened the risk of dependency and dementia, leading to poor prognosis ( 43 ), also, dementia was a risk factor of FOG ( 15 ). Patients with PD with the PIGD subtype had higher resting metabolic rates and lower body fat, which means patients with the PIGD subtype may more likely to experience weight change ( 44 ), and PIGD was identified as a possible risk factor for FOG. What is more, unexplained weight change especially weight loss was correlated with non-dopaminergic symptoms such as gait and balance disorders ( 45 ).…”
Section: Discussionmentioning
confidence: 99%